AB0363 TREATMENT PATTERNS IN RHEUMATOID ARTHRITIS PATIENTS INITIATING DMARDS: ANALYSIS OF US HEALTH PLAN CLAIMS. (June 2019) - Dore, Robin K.; Antonova, Jenya; Hill, Jerrold
Abstract : Background: The ACR treat-to-target approach for rheumatoid arthritis (RA) recommends regular assessments of disease activity and adjustment of medication regimen until efficacy goals are met. 1 Given recent advances in pharmacologic therapy, this study assessed recent treatment patterns in RA patients with a newly-initiated DMARD. Objectives: To describe current treatment patterns among RA patients initiating their first DMARD treatment. Methods: Adults with ≥2 RA claims, initiating the first DMARD between 1/2012–9/2016 (index date; ID) were identified in fully-adjudicated commercial medical and pharmacy health insurance claims (includes self-insured, full-risk, and Medicare policies for approximately 40 million lives annually). Those with 12-months continuous enrollment pre- and post-ID and without DMARD claims 12 months pre-ID were selected. Initiation of conventional synthetic DMARDs (csDMARDs), tumor necrosis factor inhibitors (TNFi), anti-interleukin-6 pathway antibodies (anti-IL6), other biologic DMARDs (bDMARDs), and janus kinase inhibitor (JAKi), as monotherapy or in combination with csDMARDs was summarized with descriptive statistics. Median therapy duration was assessed with the Kaplan-Meier method. End of treatment was defined as drug discontinuation, switch to a new therapy, or addition of another DMARD. Results: Among 26, 808 identified patients (74.2% female; mean age 51.9±11.0 years), 97.7% initiated monotherapy and 2.3% started combination therapy. The most commonly-prescribed monotherapies were csDMARD (91.3%) and TNFi (6.6%). The most commonly-prescribed combination therapies included TNFi+ csDMARDs (88.0%) and other bDMARDs+ csDMARDs (7.3%). The median duration of csDMARD monotherapy was 230 days. The median treatment duration (combination vs monotherapy) was: 225 vs. 206 days (TNFi), 227 vs. 203 days (anti-IL6), 198 vs. 182 days (other bDMARDs), and 347 vs. 301 days (JAKi) (Table). JAKi treatment had the longest therapy duration when combined with csDMARDs (347 days), and other therapies lasted for median 198-230 days. As monotherapy, JAKi duration lasted for median 301 days, and other monotherapies lasted for median 182-227 days. Conclusion: Real-world data from US longitudinal healthcare claims showed that in RA patients newly initiating DMARDs, the median duration of therapy was less than a year, suggesting a need for treatment with improved response durability. Duration of JAKi therapy was longer than the median duration of other therapies. Further research is needed to determine the reasons for the longer persistence of JAKi therapy and why persistence is low with RA therapies overall. References: [1] Singh JA, et al. 2015 American College of Rheumatology Guideline for the Treatment of Rheumatoid Arthritis. Arthritis Rheumatol. 2016 Jan;68(1):1-26. Disclosure of Interests: Robin K Dore Grant/research support from: Gilead Sciences, AbbVie, Amgen, Lilly, Pfizer, Regeneron, Sanofi, Consultant for: AbbVie, Amgen, Lilly, Speakers bureau: AbbVie, Amgen, Lilly, Sanofi, Regeneron, Pfizer, UCB, Jenya Antonova Shareholder of: Gilead Sciences, Employee of: Eli Lilly and Company, Medimmune, Genentech, Gilead Sciences, Jerrold Hill Grant/research support from: Gilead Sciences